2020
DOI: 10.2106/jbjs.19.01281
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Wide-Awake, Local-Anesthetic, No-Tourniquet Surgical Procedures Do Not Impair Driving Fitness

Abstract: Background: The use of wide-awake, local-anesthetic, no-tourniquet (WALANT) surgical techniques is increasingly common, and patients commonly ask whether they may drive home following these procedures. The impact of a numb hand and bulky dressing on driving fitness is unknown, and there is no literature to guide surgeons when counseling these patients. Thus, the primary objective of the present study was to determine driving fitness following a modeled-WALANT procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…An a priori power analysis was performed using data from a previous study by our group 15 . The mean acceleration was used as the basis for the power analysis, as it is the most sensitive and easily interpreted measure to assess reckless driving behavior 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An a priori power analysis was performed using data from a previous study by our group 15 . The mean acceleration was used as the basis for the power analysis, as it is the most sensitive and easily interpreted measure to assess reckless driving behavior 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…To test our primary hypothesis, a noninferiority analysis was performed for each kinematic metric and was compared with limits that were set prior to data collection, predetermined by the researchers to be practically substantial (see Appendix 5). Using our previously described linear mixed-effects model estimates of the difference in driving fitness between baseline and postoperative drives, Bonferroni-corrected (56 total comparisons) 95% confidence intervals (CIs) of the model estimates for changes in driving from baseline were constructed 15 . A kinematic metric was deemed inferior if the 95% CI included the corresponding noninferiority limit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The waiting time for surgery has decreased. [17] It is more difficult for patients to tolerate the technique of WALANT psychologically. [12,18] Patients have excellent compliance when informed about the benefits of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson Orfeld et al demonstrated that, following a unilaterally modelled WALANT procedure, patients' driving skills were not negatively impacted. This suggests it could be safe to drive home following a procedure under WALANT, which is not the case with other types of anesthesia [64]. Kang et al and Iqbal et al found patients who underwent CTR with WALANT reported similar postoperative functional outcomes as compared with comparison groups who received general anesthesia or wide-awake anesthesia with a tourniquet [62,65].…”
Section: Return To Functioningmentioning
confidence: 99%